2008
DOI: 10.1111/j.1559-1816.2008.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Violence in Ideological and Non‐Ideological Groups: A Quantitative Analysis of Qualitative Data1

Abstract: Multiple models have been proposed to account for violence among ideological groups. To identify critical variables contributing to violent behavior in these groups, violent ideological groups were compared to relevant comparison groups. A historically based content analysis was conducted to assess these groups with respect to a number of variables examining leader, group, organizational, and environmental attributes held to influence violence. Discriminant analyses revealed that violent ideological groups dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 67 publications
(82 reference statements)
3
35
0
Order By: Relevance
“…In the face of ongoing revelations about misbehavior in organizations by both workers (Brown 2000(Brown , 2005Greenberg 1990) and leaders (Ashforth 1994;Mumford et al 2007Mumford et al , 2008Tepper 2000) and by corporate actors (Brown 2004;Donaldson 1989) and politicians (Brown and Jones 2000) there is a continuing need to reappraise the agenda for research on ethics and identities. Perhaps surprisingly, relatively little of the huge volume of extant works on unethical, ''dark side'' and misbehavior in and around organizations has centered on identity issues.…”
Section: Leadership Ethics and Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the face of ongoing revelations about misbehavior in organizations by both workers (Brown 2000(Brown , 2005Greenberg 1990) and leaders (Ashforth 1994;Mumford et al 2007Mumford et al , 2008Tepper 2000) and by corporate actors (Brown 2004;Donaldson 1989) and politicians (Brown and Jones 2000) there is a continuing need to reappraise the agenda for research on ethics and identities. Perhaps surprisingly, relatively little of the huge volume of extant works on unethical, ''dark side'' and misbehavior in and around organizations has centered on identity issues.…”
Section: Leadership Ethics and Identitymentioning
confidence: 99%
“…Leaders' aspirations, relationships to others, day-today practices, decisions, and behaviors have all been shown to have a moral component. We know that leaders can commit unethical acts either intentionally or unintentionally (Eubanks and Mumford 2010;Mumford et al 2007Mumford et al , 2008, but outstanding questions remain as to the role of identity in decisions that are made. Exploring these issues may include delving into leaders' early life and early career experiences in the formation of identity (Ligon et al 2008), or instead, studying leadership theories and training sessions as attempts to shape, regulate, and control managers' identities as ethical beings (Waples et al 2008).…”
Section: Leadership Ethics and Identitymentioning
confidence: 99%
“…The relatively low cost and ease of creating and maintaining a webpage and minimal hindrance from regulators and law enforcement make the Internet a fertile medium for groups which advocate extreme ideologies (McCann, 2010). An ideology has been defined as a set of beliefs, values, and goals that are socially shared and held by a group as inherently good and right (Blau, 1964;Mumford et al, 2008;Van Dijk, 2006). The prevalence and popularity of ideological groups is thought to be due to the structure the group offers for its members by providing clear guidelines for understanding lived experiences (Mumford et al, 2008).…”
Section: Online Ideological Groupsmentioning
confidence: 99%
“…Contrary to common assumptions, many people who join extremist groups are not mentally ill (Victoroff, 2005;Waller, 2007), but become socialized through creating and maintaining relationships with ideological groups and their members, thus fulfilling social and psychological needs for the individual (Hogg, Meehan, & Farquharson, 2010;Mumford et al, 2008;Taylor & Louis, 2004). This process of socialization can be powerful in shaping values, beliefs, and actions, and can lead ordinary people to perform cruel and violent behaviors (Mogahaddam, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Angie et al, 2011;Coffey & Woolworth, 2004;Faulkner & Bliuc, 2016;Moghaddam, 2005). Dehumanisation of perceived of out-group members has also been associated with attempts to foster a sense of moral righteousness or moral disengagement (Cammaerts, 2009;Faulkner & Bliuc, 2016) and the creation of a sense of in-group superiority (Bliuc, McGarty, Hartley, & Muntele Hendres, 2012;Mumford et al, 2008). For instance, Faulkner and Bliuc (2016) found that racists used moral disengagement strategies such as dehumanisation to justify expressions of their views.…”
Section: Discussionmentioning
confidence: 99%